What does Shulkin's firing mean for the VA? - Robbins RA (Southwest Journal of Pulmonary and Critical Care, 2018)
No abstract available. Article truncated at 150 words. David Shulkin MD, Secretary for Veterans Affairs (VA) was finally fired by President Donald Trump ending long speculation (1). Trump nominated his personal physician, Ronny Jackson MD, to fill Shulkin’s post. The day after his firing, Shulkin criticized his firing in a NY Times op-ed claiming pro-privatization factions within the Trump administration led to his ouster (2). “They saw me as an obstacle to privatization who had to be removed,” Dr. Shulkin wrote. “That is because I am convinced that privatization is a political issue aimed at rewarding select people and companies with profits, even if it undermines care for veterans.” Former Secretary Shulkin’s tenure at the VA has had several controversies. First, as undersecretary of Veterans Healthcare and later as secretary money appropriated to the VA to obtain private care under the Veterans Access, Choice, and Accountability Acts of 2014 and the VA Choice and Quality Employment Act of …